Determinants of household debt in Asia Pacific region using panel data analysis - Azlan, Atiqah (2020)
Households Debt cases rising each year in every countries. The purpose of this study is to identify the determinants of Households Debt (more specifically Lending Interest Rate, GDP Growth, Urban Population, Tertiary Enrolment and Tax Revenue). Does these variables gives a big impact to Households Debt ? The data was collected on yearly basis form 1988 until 2018 which is 30 years of period and to test whether these variables are significant or not significant towards Households Debt. The relationships of these variables and Households Debt will be tested using Panel Regression Random Effect Model. Secondary data from reliable sources will be gathered.